Teacher Professional Education Program in Islamic Religious Education: Bibliometric Analysis and Review - Evendi, Erpin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The current study aims to explore studies related to teacher professional education programs in Islamic religious education. More specifically, it is conducting an analysis of study trends on the theme of teacher professional education programs in Islamic religious education, and reviewing several articles, especially those related to the competence of professional Islamic religious education teachers. The method used is bibliometric analysis. SCOPUS was used as the study database, descriptive and narrative analyzes were carried out based on data related to the theme of this study. Keyword filtering is carried out on the search document menu, this is intended to obtain adequate data and in accordance with the study theme. Each data displayed by SCOPUS is analyzed (analyze search results). This includes documents by year, documents by affiliation, documents by country, documents by type, and documents by subject area. The visualization of the result data is taken from the SCOPUS page and printed on the screen (to show the authenticity of the result data). Next, the author reviews two related articles that are most relevant to the teacher professional education program in Islamic religious education, and represents other articles within the scope of this study. The results of bibliometric analysis show that until now studies related to teacher professional education programs in Islamic religious education are still intensively carried out, this refers to the SCOPUS database related to the theme of the study. The main factor is Islamic religious education which is increasingly receiving international attention in line with the fundamental concepts that Islam teaches about lifelong learning, and is currently leading to professional teaching assignments. The results of the article review show that the importance of the sustainability of teacher professional development in Islamic religious education. If similar programs are not implemented in a sustainable manner, it is feared that the commitment of teachers in developing their professionalism will decrease. This study has important implications for the development of a number of literatures and studies, that the implementation of the program to increase the competence or professionalism of teachers in Islamic religious education needs to be explored further, especially the evaluation of its implementation or the competencies expected for the sustainability of Islamic religious education teacher professional education.